Recent progress in noble-metal-free electrocatalysts for alkaline oxygen evolution reaction - Tan, Deming; Xiong, Hao; Zhang, Tao; Fan, Xuelin; Wang, Junjie; Xu, Fei (Frontiers in Chemistry, 2022)
Hydrogen is regarded as an alternative of clean energy due to its high-density energy and non-polluting nature. The practical application of splitting water to generate hydrogen is to a large extent hindered by oxygen evolution reaction (OER) process. Electrocatalysts with low-cost, high activity and durability are essential for the low kinetic threshold of the OER. Despite of the high active performances of noble metals compound electrocatalysts like IrO2 and RuO2, they are heavily restricted by the high-cost and scarcity of noble metal elements. In this context, noble-metal-free electrocatalysts have acquired increasing significance in recent years. So far a broad spectrum of noble-metal-free electrocatalysts has been developed for improved OER performance. In this review, recent progress in designing and synthesizing of noble-metal-free alkaline OER electrocatalysts are briefly summarized. Finally, perspectives are also provided on the future development of alkaline OER on fabrication and evaluation of alkaline OER electrocatalysts.